Extend Product Shelf Life to Minimize Customer Complaints by Using Selected Packaging Materials - Rusman, Oktalia (International Journal of Integrated Engineering, 2024)
The majority of complaints received by PT XYZ were related to the quality of products not meeting the promised age, particularly regarding the discrepancy between actual and claimed product shelf life on wafer roll packaging. This research employed a descriptive quantitative approach utilizing an 8D methodology integrated with various Quality Management Systems (QMS) tools to identify the root cause of customer complaints. Additionally, the Sorption Isotherm Method was utilized for theoretically accelerated shelf-life testing aimed at designing more efficient packaging solutions. The main goal was to reduce complaints by implementing a tailored Quality Management System. The findings indicated that the existing plastic types (PET12/INK/ADH/VMPET12/ADH/LLDPE 50), with a WVTR value of 0.5 g H2O/m². day, were not suitable for wafer roll products with a 15-month product life. Conversely, alternative packaging materials with a permeability value of 0.0032125 g H2O/m². day. mmHg and WVTR value ≤ 0.1596 g/m²/24 hours were identified as capable of achieving the desired product shelf life. This approach significantly reduced customer complaints related to product shelf life by selecting appropriate packaging materials for wafer roll products. Following the implementation of the task force project, complaints decreased from 7 cases to 0 cases of customer complaints regarding soggy wafer roll products at PT XYZ observed within 12 months.